Komunikasi Interpersonal dan Keterampilan Memberi Penguatan: Sebuah Analisa Korelasional terhadap Minat Belajar Siswa - Mufidah, Imroatul; Asmawi, Asmawi (PALAPA: Jurnal Studi Keislaman dan Ilmu Pendidikan, 2017)
Learning should be a priority for achieving success. To realize learning activities as a priority, it takes a high interest. One effort to increase interest in learning is through interpersonal communication and strengthening skills. Therefore, researchers try to examine the relationship of interpersonal communication and strengthening skills with student interest in learning. This research uses quantitative approach (correlation research). The population of this research were 248 students of class VII of SMP Negeri 1 Pungging, and the sample in this research were 50 students. Data collection using questionnaires, interviews, and documentation. The three instruments are used to explore data on: 1) interpersonal communication, 2) strengthening skills, 3) interest in learning. The results of this study show: 1) There is a correlation between interpersonal communication with interest in learning (2.091> 2.011); 2) There is a relationship between strengthening skills with interest in learning (3.289> 2.011); 3) There is a relationship between interpersonal com- munication and strengthening skills with interest in learning (6,787> 3,20). The benefits of this research include: 1) For schools to create an environment that can increase student learning interest, 2) For teachers to motivate in improving student learning interest, 3) For students to raise awareness about the importance of learning interest.